2016
DOI: 10.1245/s10434-016-5307-z
|View full text |Cite
|
Sign up to set email alerts
|

Coexistent Loss of the Expressions of BRCA1 and p53 Predicts Poor Prognosis in Triple-Negative Breast Cancer

Abstract: Combined expression patterns of BRCA1 and p53 could serve as useful prognostic markers in TNBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…The loss of BRCA1 expression was observed in about 20% of patients and was correlated with a poor prognosis in this study. These findings are consistent with those of previous reports [ 17 , 18 ], although no association was noted between the resistance to taxanes and the loss of BRCA1 expression in this study. The EMT phenotype is considered to be related to chemoresistance.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The loss of BRCA1 expression was observed in about 20% of patients and was correlated with a poor prognosis in this study. These findings are consistent with those of previous reports [ 17 , 18 ], although no association was noted between the resistance to taxanes and the loss of BRCA1 expression in this study. The EMT phenotype is considered to be related to chemoresistance.…”
Section: Discussionsupporting
confidence: 94%
“…Among DNA repair-related genes, low expression of BRCA1 or “BRCAness” features is correlated with taxane resistance [ 14 – 16 ] and a poor prognosis, specifically TNBC [ 17 , 18 ]. Regarding EMT, we previously reported that vimentin, the major EMT-related factors, is poor prognostic factors for TNBC [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…We examined p53 expression in 156 cases of TNBC and found it was positive in 71.3% of cases, which was in consistent with reported positivity rates of p53 expression (56% to 71%) in TNBC [ 22 ]. Although the association between p53 and clinical features varies in studies, we found that histologic grade was the only variable correlated with p53 expression.…”
Section: Discussionsupporting
confidence: 86%
“…Although various methodological and clinical settings have been applied to explore p53 status for predicting therapy response and patients’ outcomes, results are contradictory [ 20 ]. Missense mutation of P53 gene induces stable detectable mutant p53 protein, whereas truncating P53 gene mutations yields unstable p53 proteins that cannot be detected by IHC [ 21 , 22 ]. Besides, wildtype p53 may accumulate in cells resulted from DNA damage or binding to other proteins and thus show strong immunoreactivity [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a strong association between BCCIP negativity and normal p53 status, or p53 mutant status with a normal level of BCCIP (Table 1 , p = 0.0018, χ 2 test). This is in contrast to the breast cancers of BRCA1 deficiency, which are often associated with p53 mutations [ 5 , 8 10 , 41 ]. We also examined BCCIP expression in 12 cases of TNBC with BRCA1 mutations, and found that only one of the 12 cases was BCCIP negative (8%), which is significantly less frequent than in sporadic TNBC (49%, p = 0.0073, χ 2 test).…”
Section: Resultsmentioning
confidence: 94%